ANALISIS KOMODITAS DAN SUBSEKTOR UNGGULAN SEKTOR PERTANIAN PROVINSI MALUKU UTARA - Karmila Ibrahim; Slamet Hartono; Irham Irham (Agro Ekonomi, 2008)
The study purpose: (1) to know the leading sub-sector and leading agricultural commodity; and (2) to know the agricultural sector growth in North Maluku province in 2000-2006. This study use PDRB data based on constant price in 2000 and commodity production value. Analyses used are LQ, DLQ, Shift-Share, and Klassen Typology. The results show that agricultural sector values, includes food crops, estate, forestry sub-sector, have LQ and DLQ value more than 1, means that those sub-sector leads. On the other hand, agricultural leading commodity are paddy, corn, groundnut, yam, cassava, clove, nutmeg, coconut, lay hen, broiler, goat, cow, group of timber tree, back woods, and number of fishes, that are origin community called as fish beloso, fish biji nangka, fish kuwe, fish swanggi, white pomfret, mackerel, fish sunglir, fish terbang, fish julung-julung; tiny sefish, terubuk, fish cakalang, barong shrimp, squit, cuttlefish, and terrapin.The growth rate of agricultural sector in North Maluku province wasaffected by national growth rate. The growth rates of agricultural sectordistrict before and after decentralization are affected by the growth rate ofprovince. Based on Klassen Typology, North Maluku was classified as poorregion at national level.